Mental health and decision-making participation of adolescent orphans: A pilot study - Annette d'Arqom; Farhan Nurdiansyah; Danti Nur Indiastuti; Mhd Zamal Nasution; Nurmawati Fatimah; Sri Purwaningsih; Yuani Setiawati; Kusuma Eko Purwantari (Faculty of Nursing Universitas Padjadjaran, 2023)
Background: Mental health has been brought to attention lately, with the increase of mental health problems during adolescence. In Indonesia, it is reported that one-third of adolescents develop mental health disorders. Childhood grief, separation from the family, child labor, or abuse affect the orphans’ mental health, including their decision-making participation. Purpose: As a pilot study, this study would like to investigate the mental health conditions and decision-making participation among orphans in one orphanage in Mojokerto district, East Java, Indonesia.Methods: This cross-sectional study utilizes the Depression Anxiety Scale Youth version (DASS-Y) and Child and Adolescent Participation in Decision Making Questionnaire (CAP-DMQ). Thirty-five adolescent orphans of one orphanage in Mojokerto were recruited using convenience sampling. The frequency of respondents’ mental health and decision-making participation were measured, and the mean differences between each group of sociodemographic factors were measured using the Mann-Whitney U test or the Kruskal Wallis test. Association between mental health and decision-making participation was calculated using Chi-square test.Results: The results show that 40% of respondents were categorized as having mild mental health problems, including depression, anxiety, and stress. Mental health problems are mostly found in males (22.90%) and elementary school (20%). The participation of the orphans in decision-making is considered good, with a median of 25.5. The bivariate analysis concludes the association between anxiety, age, grade, and decision-making participation (p= 0.024, p= 0.029, p=0.029, respectively).Conclusion: Taken together, attention to orphans, especially adolescents, and their problems are necessary to reduce the health discrepancies within these vulnerable groups. Broader respondents are needed to understand the complete picture of mental health conditions among Indonesian adolescent orphans, including late adolescents.